2020
DOI: 10.1101/2020.07.02.185645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a free radical scavenging probiotic to mitigate coral bleaching

Abstract: ABSTRACTCorals are colonized by symbiotic microorganisms that exert a profound influence on the animal’s health. One noted symbiont is a single-celled alga (from the family Symbiodiniaceae), which provides the coral with most of its carbon. During thermal stress, the algae’s photosystems are impaired, resulting in a toxic accumulation of reactive oxygen species (ROS) that cause cellular damage to both the host and symbiont. As a protective mechanism t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Labrenzia is part of the core microbiome of the anemones' Symbiodiniaceae (Lawson et al, 2017) and may have a role in the production of antioxidants such as dimethylsulfoniopropionate (DMSP) and its breakdown products (Sunda et al, 2002). The DMSP biosynthesis (Curson et al, 2017) and degradation genes, were found in the whole genome sequences of E. diaphana-sourced Labrenzia isolates (Dungan et al, 2020a). Sphingobacteriales in soil systems are believed to be copiotrophic, referring to their ability to metabolize a wide array of carbon sources (Hester et al, 2018).…”
Section: Potential Key Microbiome Members Of Exaiptasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Labrenzia is part of the core microbiome of the anemones' Symbiodiniaceae (Lawson et al, 2017) and may have a role in the production of antioxidants such as dimethylsulfoniopropionate (DMSP) and its breakdown products (Sunda et al, 2002). The DMSP biosynthesis (Curson et al, 2017) and degradation genes, were found in the whole genome sequences of E. diaphana-sourced Labrenzia isolates (Dungan et al, 2020a). Sphingobacteriales in soil systems are believed to be copiotrophic, referring to their ability to metabolize a wide array of carbon sources (Hester et al, 2018).…”
Section: Potential Key Microbiome Members Of Exaiptasiamentioning
confidence: 99%
“…As an alternative approach to creating the MM, we have explored a community reduction strategy of the E. diaphana microbiome by manipulating the external environment (Clavel et al, 2017), instead of the application of antibiotics. Studies on the microbiome of E. diaphana indicate a similar phylum level diversity to corals (Blackall et al, 2015) for anemones sourced from the Great Barrier Reef (GBR) (Hartman et al, 2019(Hartman et al, , 2020Dungan et al, 2020a), Hawaii (Herrera et al, 2017), Pacific and Caribbean (Brown et al, 2017), Atlantic (Röthig et al, 2016), and Red Sea (Ahmed et al, 2019). We hypothesize that selective forces acting on E. diaphana and its microbiome, when placed in sterile seawater, will reduce the complexity of the microbiome with the loss of some (e.g., transient) members.…”
Section: Introductionmentioning
confidence: 98%
“…117 and Marinomonas ostreistagni 118 among others. Other microorganisms like Alteromonas portus 119,120 and Seonamhaeicola algicola 121,122 are known for production of antioxidants carotenoids, zeaxanthin; Alteromonas oceani 123 and Ruegeria sp. 115 for probiotics; Alteromonas portus 120 for anticancer activity;…”
Section: Discussionmentioning
confidence: 99%
“…Alteromonadaceae belong to a diverse group of heterotrophic gammaproteobacteria known to associate with marine hosts and nutrient rich environments. Members of this group tolerate relatively high temperatures and have been used in coral probiotic studies as coral-associated bacteria capable of scavenging free radicals (Dungan et al 2020), and therefore could provide similar benefits in shallow, high-light environments. Similarly, Acidimicrobiales are known to be planktonic free-living photoheterotrophs found in both temporal and tropical photic zones (Angly et al 2016) and are associated with DOM in marine environments (Osterholz et al 2018).…”
Section: Microbiome Communities Vary Across Depths and Are Enriched In Shallow Habitatsmentioning
confidence: 99%